Transition in Patients with Congenital Heart Disease in Germany: Results of a Nationwide Patient Survey - Helm, Paul C.; Kaemmerer, Harald; Breithardt, Günter; Sticker, Elisabeth J.; Keuchen, Roland; Neidenbach, Rhoia; Diller, Gerhard-Paul; Tutarel, Oktay; Bauer, Ulrike M. M. (Frontiers in Pediatrics, 2017)
Background: A growing number of adults with congenital heart disease (ACHD) pose a particular challenge for healthcare systems across the world. Upon turning 18, under the German national health care system, ACHD patients are required to switch from a pediatric to an adult cardiologist or an ACHD certified provider. To date, reliable data investigating the treatment situation of ACHD patients in Germany are not available. Material and methods: An online survey was conducted in collaboration with patient organizations to address the life situation and the conditions of health care provision for ACHD patients in Germany. ACHD patients were recruited from the database of the National Register for Congenital Heart Defects (NRCHD) and informed about the survey via email, websites and social networks. A total of 1,828 ACHD patients (1,051 females) participated. The mean age was 31.7±11.7 years. Participants were surveyed about the treating physicians and the institution mainly involved in the treatment of their congenital heart disease. In addition, participants were asked questions to assess the level of trust towards their treating physician and their familiarity with the term “ACHD-certified provider”. Results: Among the surveyed patients, 25.4 % stated that they attend a specific ACHD clinic at a heart center regularly, 32.7 % were treated in a private practice setting by a pediatric cardiologist, 32.4 % in a private practice (adult) cardiology setting and 9.5 % were treated by an “other physician”. Only 24.4 % of the male and 29.7 % of the female ACHD patients were familiar with the term “ACHD-certified provider”. Conclusions: The transfer from pediatric cardiology to ACHD care requires further attention as many adult patients have not transferred to certified ACHD providers. The question of whether ACHD patients in Germany are offered consistent and adequate care should also be investigated in more detail. The answers regarding the ACHD certification are particularly disappointing and indicative of a large information gap and inadequate education in clinical practice.